Desenvolvimento de software de simulação de fluidos utilizando o método Smoothed Particle Hydrodynamics - Boszczovski, Pedro Henrique Pìantoni (2022)
Numerical methods are largely used to solve complex natural physical problems and phenomena that do not have an analytical solution. Its approach approach enables the resolution of technical and scientific problems with high fidelity of results. The “Smoothed Particle Hydrodynamics” (SPH) method or Smoothed Particle Hydrodynamics is a method whose origin derives from the study of astrophysical problems with behavior similar to that of fluids. Therefore, it is currently a powerful tool capable of solving major problems related to fluid dynamics, used by academia and commercial functions. The method is Lagrangian and does not depend on a numerical mesh, which is responsible for reading information at each instant of time, but on the fact that small particles, discretized in the domain, carry their own physical information such as velocity, position, temperature, etc., during the necessary time. A program was coded in Fortran based on the numerical method, its validation took place using the Poiseuille flow analytical formula, and it obtained results above ninety percent of accuracy in general.